An extension of the Derrida–Lebowitz–Speer–Spohn equation. (6th November 2015) - Bordenave, Charles; Germain, Pierre; Trogdon, Thomas
Abstract: We show how the derivation of the Derrida–Lebowitz–Speer–Spohn equation can be prolonged to obtain a new equation, generalizing the models obtained in the paper by these authors. We then investigate its properties from both an analytical and numerical perspective. Specifically, a numerical method is presented to approximate solutions of the prolonged equation. Using this method, we investigate the relationship between the solutions of the prolonged equation and the Tracy–Widom GOE distribution.